2018–2019 Florida Citrus Production Guide: Brown Rot of Fruit - Megan M. Dewdney; Evan G. Johnson; James H. Graham (EDIS)
Management of brown rot, caused by Phytophthora nicotianae or P. palmivora, is needed on both processing and fresh market fruit. While the disease affects all citrus types, it is usually most severe on Hamlin, Navel, and other early maturing sweet orange cultivars. This 2-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Megan M. Dewdney, Evan G. Johnson, and James H. Graham, and published by the Plant Pathology Department, May 2018.